PENGEMBANGAN BAHAN AJAR MENULIS BERITA BERDASARKAN PENDEKATAN PROSES GENRE - Wismanto, Agus (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to (1) describe the needs of textbooks in learning to write news writing which are used as development teaching materials, (2) design textbooks that are in accordance with the analysis of student needs, (3) develop text books for writing news writing based on a genre process approach for students at the Indonesian Language and Literature Education Study Program, Faculty of Language and Letters, University of PGRI Semarang, (4) to find out the potential influence of developing news writing text books based on the genre process approach to learning outcomes. This research is research and development. The subjects in this study were 26 students of the Indonesian Language and Literature Education Study Program, Faculty of Language and Art, University of PGRI Semarang. The results of the study indicate that the news writing text book as a result of this development has a potential influence in improving students' abilities and understanding of news writing materials in university.